2021
DOI: 10.3390/ma14164401
|View full text |Cite
|
Sign up to set email alerts
|

In-Line Observation of Laser Cladding Processes via Atomic Emission Spectroscopy

Abstract: Direct metal deposition (DMD) can be used for the cladding of surfaces as well as repairing and additive manufacturing of parts and features. Process monitoring and control methods ensure a consistent quality during manufacturing. Monitoring by optical emission spectroscopy of the process radiation can provide information on process conditions and the deposition layer. The object of this work is to measure optical emissions from the process using a spectrometer and identify element lines within the spectra. Si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 37 publications
(33 reference statements)
1
3
0
Order By: Relevance
“…Higher energy input led to increasing vaporisation and the depletion of Cr atoms from the melt pool [29]. Similar effects could be observed during a recently published study [30]. Co-Cr-powder was cladded on mild steel substrate with a coaxial powder nozzle and a 4 kW diode laser.…”
Section: Optical Emission Spectroscopy (Oes) In Laser Welding Processessupporting
confidence: 79%
See 1 more Smart Citation
“…Higher energy input led to increasing vaporisation and the depletion of Cr atoms from the melt pool [29]. Similar effects could be observed during a recently published study [30]. Co-Cr-powder was cladded on mild steel substrate with a coaxial powder nozzle and a 4 kW diode laser.…”
Section: Optical Emission Spectroscopy (Oes) In Laser Welding Processessupporting
confidence: 79%
“…Single spectra are sorted into two categories -Type-A and Type-B. This has been published in previous work [30]. Type-A spectra show at least one detectable peak whereas Type-B spectra merely feature thermal background radiation without any detectable peaks.…”
Section: Spectroscopic Measurementsmentioning
confidence: 99%
“…In contrast, chromium is predominantly contained in the powder material (26.7 wt.%) and only to a negligible extent in the substrate material (0.03 wt.%). In a previous study (Ref 20), it was already found that emission lines occur mainly in the presence of a melt pool. Experiments with an isolated laser-powder interaction showed no significant emissions.…”
Section: Cross-sectional Dimensions and Spectroscopic Analysismentioning
confidence: 91%
“…The relationship model between the elements' weight ratio and the intensity ratio of spectral lines was built, which indicated that the elements' weight ratio in the coating was directly affected by the variation of input energy density during processing. Schmidt et al [11] used a spectrometer to measure the light emission during laser cladding and identify the element lines in the spectrum. The results revealed that the measurement of line or spectral intensity can be used for on-line monitoring of the laser cladding dynamic process.…”
Section: Introductionmentioning
confidence: 99%